2022
DOI: 10.6065/apem.2244038.019
|View full text |Cite
|
Sign up to set email alerts
|

Remission in pediatric Graves’ disease treated with antithyroid drug and the risk factors associated with relapse

Abstract: Purpose: To evaluate the characteristics and frequency of remission in pediatric patients with Graves’ disease (GD) treated with antithyroid drug (ATD) and to identify factors that may be associated with relapse.Methods: Medical records of patients younger than 19 years who presented to the Department of Pediatrics of Queen Elizabeth Hospital Hong Kong with newly diagnosed GD from 1st January 2007 to 31st December 2017 were retrospectively reviewed. Remission was defined as euthyroidism for 12 months or more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Several studies over the past few decades have explored the efficacy and safety of long-term ATD therapy in children [14,15,[17][18][19]. A randomized trial comparing long-term (96-120 months) MMI treatment with short-term treatment (18-24 months) in pediatric GD found significantly higher remission rates in the long-term group: 92% at 1 year and 88% at 4 years post-MMI withdrawal, versus 46% and 33% in the short-term group, respectively [18].…”
Section: Main Textmentioning
confidence: 99%
“…Several studies over the past few decades have explored the efficacy and safety of long-term ATD therapy in children [14,15,[17][18][19]. A randomized trial comparing long-term (96-120 months) MMI treatment with short-term treatment (18-24 months) in pediatric GD found significantly higher remission rates in the long-term group: 92% at 1 year and 88% at 4 years post-MMI withdrawal, versus 46% and 33% in the short-term group, respectively [18].…”
Section: Main Textmentioning
confidence: 99%
“…In this study [ 8 ], the authors studied 81 Chinese children treated with ATD and reported that 17.8% experienced remission and 57.4% experienced relapse after discontinuation of ATD. In addition, although the remission rate through ATD treatment was low in Asian children with GD, the longer was the ATD treatment period, the higher was the remission probability.…”
mentioning
confidence: 99%